PENGARUH KUALITAS AUDIT, VOLUNTARY DAN TIMELY DISCLOSURE TERHADAP BIAYA UTANG - Nadia Yuli Widyastuti; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2020)
The aim of this reasearch is to analyze the effect of audit quality, voluntary disclosure and timely disclosure on cost of debt, using control variable such as size, loss, and earnings variability. Cost of debt is measured using interest expense scaled by long and short therm liabilities. This research uses quantitative method by using multiple linear regression analysis. The population of this research is all company manufacturing consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) in the period 2014-2018. The sample is selected using purposive sampling method and acquired 125 firms.The result showed that audit quality, timely disclosure, loss and earnings variability does not significantly influence on cost of debt. By contrast, the association between voluntary  disclosure and size significantly influenced cost of debt.